The inclusion of children with Down syndrome in the school environment - Almeida, A. K. S.; Moraes, S. F. S.; Lopes, T. (Scientific Electronic Archives, 2017)
This research has the overall objective to cause a reflection on the limits and possibilities of including children with Down syndrome in regular schools. For the study was used conducted field research and literature, with a qualitative approach, applying Â for the better development of the research a questionnaire with open questions for the teacher, and we used the inductive method. The research is supported by SASSAKI studies (1997); Ferreira (2005); SCHWAARTZMAN (1999), among others discuss the proposal of this research. Inclusion is discussed in this paper as a possibility of stay of students with disabilities in school, his stay so that is makes possible its development and the construction of know ledge. Therefore, in this study high light the importance of knowing and discussing the inclusion of children with Down syndrome in the regular school system where their rights must be guaranteed and ensured.